Analysis of The Influence of Human and Technical Factors in Mooring ‎Rope Accidents in Ship Operations at The Ports of Indonesia - Kundori , K.; Mawardi, Kholid; Khamdilah, Ali; Rosita, Niken Devi; Hermawati, Renny; Kristiyanti, Mariana (International Journal of Basic and Applied Sciences, 2025)
Ship mooring operations at the port are one of the critical activities on board a ship that ‎involves the use of mooring lines to secure the position of the ship while at the dock. This study ‎aims to identify various human and technical factors that contribute to mooring line accidents ‎during ship operations at the port, evaluating how effectively the safety management system ‎is implemented in Indonesian ports. This study uses a mixed-methods approach regarding the ‎influence of human and technical factors in mooring line accidents on ship operations at the port. ‎The study population includes all personnel involved in ship mooring operations at four ports in ‎Indonesia. The results show that operational time pressure has a strong total effect (0.73) on ‎communication errors through the mechanism of fatigue. In addition, a weak safety culture ‎contributes significantly to material failure (0.60) through inadequate maintenance. The strong ‎correlation between lack of training and inadequate maintenance (r=0.56) shows how ‎deficiencies in personnel competence can impact the technical aspects of mooring operations. The ‎high correlation between fatigue and operational time pressure (r=0.71) highlights the impact of ‎efficiency demands on the physical and mental condition of workers. The development of ‎standardized communication protocols and mandatory pre-operational briefings can be an ‎effective strategy to mitigate the risk of mooring line accidents in the short term, while in the ‎long term, a combination of technical, operational, management, and regulatory interventions is ‎needed to comprehensively address the risk factors‎.